Comparative study of tall building response to synoptic and non-synoptic wind action - Leandro Fleck Fadel Miguel; Jorge Daniel Riera; Vanessa Vanin (REM: International Engineering Journal)
Abstract Until the beginning of the 21st Century, the characteristics of wind for purposes of structural analysis and design, as reflected in wind codes worldwide, were based on the behavior of wind currents in the vicinity of the ground surface observed in so-called synoptic events. It was only recently recognized that the latter are not the only cause of wind damage to buildings and structures, not even its main cause. In view of the absence of any reference to non-synoptic winds in most South American wind codes, their urgent revision to include the effects on non-synoptic winds is badly needed. The downburst is a relevant meteorological phenomenon that causes extreme winds in the lower atmospheric boundary layer. The present article briefly describes an introduction to an simplified approach recently proposed by the second author to describe the wind velocity field in this type of meteorological phenomenon, that is, downbursts within instability lines. The method is examined by a comparative study of tall building response to synoptic and non-synoptic wind action.